Sport i rekreacja przy wybranych akwenach objętych zakwitami alg i sinic na przykładzie wybranych zbiorników Polski - Justyna Pacelt; Wojciech Szeligiewicz (Studia Ecologiae et Bioethicae)
The water environment constitutes a basic resource for not only human life but also recreational activity during the holiday season. In reservoirs with high trophic level caused mainly by water contamination, algal blooms occur. This phenomenon is especially intensive in spring and than in summer and affects the use of water reservoirs and coastal areas by people. One type, toxic blooms, is very dangerous for human health. If people who use the reservoir for recreational and professional purposes are unaware of the occurrence of this type of bloom, it may cause serious health problems and financial losses. To avoid this situation, cooperation among institutions which monitor water conditions on each reservoir must be established.